Evaluation of Parking Performance in the Maulana Malik Ibrahim Gresik - Mochammad Surono; Sapto Budi Wasono (LPPM of NAROTAMA UNIVERSITY, 2019)
Along with the increase number of employees and pilgrims in Maulana Malik Ibrahim Graveyard from year to year, it certainly has an impact on the increasing volume of vehicles on its parking area. The avaibility of parking area that is not proportional to the volume of vehicles will certainly disrupt the orderliness and comfort of the parking users around Maulana Malik Ibrahim graveyard. The research method used for performance analysis is in the form of field survey by using the data of two wheels and four wheels vehicle parked in that area. In analyzing this parking performance surveyed on July 1st - 5th 2018, it is found that the highest volume of two wheels vehicles is 418 vehicles, with the highest accumulation of 43 vehicles on average the highest duration 209.50 minutes / vehicle, the highest turnover is 0.804, the highest level of parking used is 80.43% and the number of available parking capacity of motorcycles is 230 plots, while the highest number of parking requests is 185 plots. Therefore, the available parking capacity for two wheels vehicle is still quite accommodating the number of vehicles parked. Meanwhile, for four wheels vehicles, it obtained that the highest volume is 442 vehicles, with the highest accumulation of 50 vehicles on average the highest duration of 115.50 minutes / vehicle, the highest turnover is 1,171, the highest level of parking used is 117.14% and the number of available car parking capacity is 140 plots, with highest number of parking requests is 165 plots. Since the number of parking lots is the highest 25 plots, so that the available parking capacity is not enough to accommodate the number of vehicles parked.